Criminal Liability of Political Parties in Spain and Philippines - Fernández-Cabrera, Marta (My University, 2018)
The Spanish Criminal Code incorporated in 2010 the criminal liability of legal persons. However, it left out certain controversial active subjects such as trade unions and political parties. Political parties are peculiar entities because, despite adopting the form of private associations, they play a clearly public role as a constitutional instrument of political participation, which requires a special commitment to respect the general social interest. For this reason, its exclusion was criticized, especially when it is widely observed that the political parties operate, often, as illegitimate lobbies, corruption spots and entities that are illegally financed or that commit electoral irregularities. Due to the pressure of doctrine and citizenship, the legislator, in its intention to satisfy social needs of the fight against corruption, decided to subject these entities to criminal liability in 2012. The purpose of this paper is to give a general view of how the criminal responsibility of political parties is configured in the Spanish Criminal Code. So, I will analyze the options of sanctioning political parties, on the one hand, through the general regime (31 bis SCC), but also through crimes which punish illicit associations (515 SCC) or criminal organizations (570 SCC). In addition, I will try to compare the Spanish situation with the Philippine legal system.
Keywords: Corrupción; Criminal liability of legal persons; Criminal liability of political parties; Corruption